Science and Digital Technology for Cultural Heritage (Milton)
1 online resource (435 p.)
Keywords: The scientific and technological advances that influence the protection of cultural heritage are developing at an ever-increasing pace. Systems to explore, research and analyse their materiality, to control the different scopes, or to represent and model them have reached an unprecedented dimension in recent decades. The Network of Science and Technology for the Conservation of Cultural Heritage aims to promote collaboration between the agents of these systems, in order to facilitate the sharing of experiences and to foster technology transfer, with the common goal of contributing to the conservation of Cultural Heritage. In the context of the TechnoHeritage Network, the fourth edition of the International Congress on Science and Technology for the Conservation of Cultural Heritage was held March 26-30, 2019, in Seville, Spain. This Congress was an international meeting of researchers and specialists from multiple areas, whose line of work is the knowledge and conservation of Cultural Heritage. Among all the topics discussed, the role and impact of digital technologies for the knowledge, maintenance, management and dissemination of cultural heritage should be highlighted. Digital media modify the way of understanding this heritage, of perceiving it and transmitting it, and offer a new horizon of strategies to make decision-making more sustainable over time.